Hubungan Tingkat Pengetahuan Ibu Post Partum Usia Muda dengan Perawatan Luka Perineum di Desa Lembengan – Jember - Nisak, Qorina Izzaty Khoirun; Nila Widya Keswara (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
Because it is prone to a number of issues, including postpartum infection, the postpartum period is an important time. Wounds in the birth canal, which provide the perfect environment for bacteria to flourish, may be the source of this infection. Further difficulties could arise if an infection in the perineal area spreads to the birth canal or urinary system. Perineal wound treatment is therefore crucial. Maternal health may suffer as a result of cultural customs that are inadequate for caring for the perineum and a lack of knowledge about moms throughout the postpartum phase. This study's objective is to determine the degree of perineal wound care knowledge among postpartum women who had a normal delivery. Descriptive study using the successive sampling technique is the methodology employed. Fourteen postpartum moms with a maximum of second-degree perineal lesions made up the sample. According to the findings, four respondents knew enough about perineal wound care, whereas ten respondents knew very little. Therefore, to enhance maternal health following childbirth and lower the risk of infection during the postpartum period, midwives must effectively educate women on how to care for their perineal wounds.